Comparative efficacy of three different heat tolerance indices for thermo-adaptability during heat stress in bovines - Vaidya, Mangesh Mahadeo; Dongre, VB; Dhenge, SA; Kokate, LS; Singh, SV (Indian Journal of Dairy Science, 2022)
The present study was conducted on 45 Marathwadi buffaloes and 24 Deoni cows of different age groups from Instructional Livestock Farm Complex at COVAS, Udgir. Â Various physiological parameters like rectal temperature, pulse rate, and respiration rate of these animals were recorded during the summer season, and efficacy of three heat tolerance indices viz. Iberia heat tolerance indices, Benezara coefficient of adaptability, and Dairy search index were estimated. Highly significant (P